The Development of Spondias pinnata (L.f) Kurz. Leaf Extract Toothpaste: Formulation, Physical Properties Evaluation and its Antibacterial Efficacy Against Streptococcus mutans Bacteria - Habibah, Nur; Bekti, Heri Setiyo; Dewi, Ni Nyoman Astika; Dharmawati, I Gusti Agung Ayu; Krisna, Luh Ade Wilan; Mahastuti, Shri Ayu Purnami (JURNAL INFO KESEHATAN, 2024)
Cemcem (Spondias pinnata (L.f) Kurz) is a native Indonesian plant that has long been used as a traditional medicine. The ethanol extract of S. pinnata contains alkaloids, carbohydrates, flavonoids, triterpenoids, steroids, tannins, resins, and saponins. It has proven antibacterial activity against gingivitis and periodontitis bacteria, such as Streptococcus mutans. This study aims to develop a toothpaste formula with the active ingredient of S. pinnata leaf extract with various concentrations of 5, 15, and 30%; evaluate its properties; and measure its antibacterial effectiveness against Streptococcus mutans. The research method used a quasi-experimental method with a post-test-only control group design. The S. pinnata leaves were extracted with 96% ethanol solvent using the maceration technique. The properties of the toothpaste were evaluated based on homogeneity, spreadability, foam height, viscosity, and pH. The liking test was conducted to assess color, taste, scent, and texture based on the perception of 30 panelists. Antibacterial activity was tested using the well diffusion method. The test results confirm that all preparation formulas are homogeneous, the foam height is in the range of 4.33 - 21.33 cm, the spreadability is in the range of 3.44 - 4.53 cm2, the viscosity of toothpaste is in the range of 20767-67600 cps, and the pH value is in the range of 4.82 - 7.59. The results showed that toothpaste containing 5% of S. pinnata leaf extract met the physical and pH requirements and was most favored by panelists. This formula also showed antibacterial activity against S. mutans with an average inhibition zone diameter of 7.72 mm ± 0.439. Based on the study's results, it can be concluded that toothpaste containing 5% S. pinnata leaf extract effectively inhibits the growth of S. mutans bacteria by 54.33% compared to the positive control. Further research is suggested to optimize the concentration of S. pinnata leaf extract to maximize its antibacterial activity, without affecting its physical quality and organoleptic acceptance.